The use of concept mapping and vee heuristics in higher education to promote critical reflection and meaningful learning - Jacqueline Vanhear (Universidad de Granada, 2013)
Higher Education is currently undergoing relentless change worldwide in order to respond effectively to the aspirations of the 21st century. Consequently, prevalent literature in Higher Education calls for more emphasis on the studentsʼ learning process through increased metacognition and critical reflection. This paper starts off with the assumption that learning takes place through the integration of thinking, feeling and acting. As a result, this paper will present a model of teaching and learning in Higher Education through the integrated use of Vee Heuristics and Concept Mapping. This research will suggest that when using Concept Maps, Vee Heuristics along with an awareness of how students prefer to learn, the students will go through a metacognitive learning process which would eventually lead to critical reflection and meaningful learning. Using University studentsʼ work products, this study traces the effect of a learnerʼs mental operations on the learnerʼs use of Vee Heuristics and Concept Mapping as the learner embeds and retrieves new and scaffolded knowledge. The data collected reveals the powerful effect which this combination of learning tolos yielded on student achievement and transformation.